The Role of Teachers in Promoting Autonomous Language Learning: The Case Of Addis Ababa Science And Technology University - Belayineh, Ababo Abebe; Kasa, Animaw Anteneh (Universitas Pendidikan Mandalika, 2025)
Nowadays promoting autonomous learning has become an important aspect of education. This study aimed to investigate the roles of the teachers in promoting autonomous English language learning at Addis Ababa Science and Technology University. Its emphasis was on the roles of facilitator, guide/mentor, and inspirator/supporter and to what extent supporting environment helping to promote autonomous language learning are available and are used effectively. A survey questionnaire was distributed to 313 freshmen engineering students at Addis Ababa Science and Technology University where 24 students participated in FGD. Furthermore, an interview was conducted with four teachers to obtain supplementary data and for triangulation. The quantitative data was analyzed using SPSS and the qualitative data obtained from FGD and interview was analyzed using thematic analysis. The findings indicate that teachers were involved in very limited practices that promote autonomous language learning and used available supporting facilities ineffectively. As facilitators, teachers did not offer necessary assistance on learning plans and objectives and in evaluating their own learning and progress. As a guide/mentor, teachersâ€™ assistance in providing alternative learning strategies and references was bound to the module and course outline.Â As an inspirator/supporter of autonomous learning teachers were weak on being positive and supportive when giving feedback, encouraging students to keep a written record of their learning, and acknowledging different ways students follow to attain their goal and their own learning styles. Hence offering teachers professional development programs on how to promote autonomous language learning will help develop learner autonomy.